Nystose attenuates bone loss and promotes BMSCs differentiation to osteoblasts through BMP and Wnt/β-catenin pathway in ovariectomized mice - Qi Zhang; Sijing Hu; Jianjun Wu; Peng Sun; Quanlong Zhang; Yang Wang; Qiming Zhao; Ting Han; Luping Qin; Qiaoyan Zhang (Food Science and Human Wellness)
Increasing the osteogenic differentiation ability and decreasing the adipogenic differentiation ability of bone marrow mesenchymal stem cells (BMSCs) is a potential strategy for the treatment of osteoporosis (OP). Naturally derived oligosaccharides have shown significant anti-osteoporotic effects. Nystose (NST), an oligosaccharide, was isolated from the roots of Morinda officinalis How. (MO). The aim of the present study was to investigate the effects of NST on bone loss in ovariectomized mice, and explore the underlying mechanism of NST in promoting differentiation of BMSCs to osteoblasts. Administration of NST (40, 80 and 160 mg/kg) and the positive control of estradiol valerate (0.2 mg/kg) for 8 weeks significantly prevented bone loss induced by ovariectomy (OVX), increased the bone mass density (BMD), improved the bone microarchitecture and reduced urine calcium and deoxypyridinoline (DPD) in ovariectomized mice, while inhibited the increase of body weight without significantly affecting the uterus weight. Furthermore, we found that NST increased osteogenic differentiation, inhibited adipogenic differentiation of BMSCs in vitro, and upregulated the expression of the key proteins of BMP and Wnt/β-catenin pathways. In addition, Noggin and Dickkopf-related protein-1 (DKK-1) reversed the effect of NST on osteogenic differentiation and expression of the key proteins in BMP and Wnt/β-catenin pathway. The luciferase activities and the molecular docking analysis further supported the mechanism of NST. In conclusion, these results indicating that NST can be clinically used as a potential alternative medicine for the prevention and treatment of postmenopausal osteoporosis.